Integration of organizational-technological and social aspects in the realization of the program of renovation of residential development - Korol Elena; Gaydysheva Yuliya; Passmore David (MATEC Web of Conferences, 2018)
The renovation program is designed to solve a complex of problems of the city, the priority of which is a comfortable ratio of building density and developed infrastructure. The draft regional standards for urban planning has been developed for a pragmatic and at the same time comfortable layout of buildings (urban blocks) with an infrastructural core. Nevertheless, such an approach contains a number of administrative risks that can be minimized by carrying out proper planning and execution within a scheduled time frame. To improve planning accuracy, it is possible to use a system-organized block diagram consisting of integrated resettlement units. To select the optimal relocation option, it is important to carry out a multivariate analysis.